Ordo - Greenslade, Canon S. L. (Scottish journal of theology, 1956)
The Church Militant, living and working in history as an organic and visible society, must have a structure and organs which express its nature and enable it to be what it is and to fulfil its function or mission. Whatever might be argued a priori about this structure and these organs, and whatever might be learned from the experiences of history through the centuries, it is plain from the New Testament that the apostolic church possessed institutions which were part of its structure and which existed in order to further its mission. Among these was a ministry of men distinguishable qua ministers from the other members of the body, a special organ of, and therefore within, the one body.